CDC27-ODC1 Axis Promotes Metastasis, Accelerates Ferroptosis and Predicts Poor Prognosis in Neuroblastoma - Qiu, Lin; Zhou, Rui; Luo, Ziyan; Wu, Jiangxue; Jiang, Hua (Frontiers in Oncology, 2022)
Neuroblastoma (NB) is a devastating malignancy threatening children’s health, and amplification of MYCN is associated with treatment failure and a poor outcome. Here, we aimed to demonstrate the role of cell division cycle 27 (CDC27), an important core subunit of the anaphase-promoting complex, and its clinical significance in NB patients. In functional assays, we illustrated that CDC27 promoted the cell growth, metastasis and sphere-formation ability of NB cells both in vitro and in vivo. To further understand the potential mechanism, SK-N-SH cells were transfected with CDC27 siRNA, and RNA-sequencing was performed. The results revealed that downregulation of CDC27 led to markedly reduced expression of ODC1, which is a well-established direct target of MYCN. Subsequently, we further illustrated that suppression of ODC1 significantly attenuated the promotion effect of CDC27 on the proliferation, metastasis, and sphere-formation ability of NB cells, hinting that CDC27 exerted its biological behavior in NB at least partly in an ODC1-dependent manner. In addition, CDC27 rendered cells more vulnerable to ferroptosis, while knockdown of ODC1 markedly reversed the pro-ferroptotic effect of CDC27. Collectively, our data is the first to report that the CDC27/ODC1 axis promotes tumorigenesis and acts as a positive regulator of ferroptosis in NB, highlighting that CDC27 may represent a novel therapeutic strategy and prognostic biomarker in neuroblastoma.